REVITALISASI PASAR TRADISIONAL PADANG LUA KECAMATAN BANUHAMPU KABUPATEN AGAM - Siska Yuliani; Zaili Rusli. SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Local Government Agam in maintaining the resilience and the existence of traditional markets has formulated a program to revitalize traditional markets listed in Regional Regulation Agam District No. 1 of 2014 on the Management of the Market and the Medium Term Development Plan of Regional Office of Cooperative Micro Small Medium Enterprises (MSME) Industry Trade in 2010 to 2015.Traditional market revitalization program is not implemented in the market Padang Lua because it is constrained by the land ownership status. Current market conditions now necessary renewal and development of the market both in terms of physical and non-physical. The problem in this research is how to revitalize traditional markets Banuhampu District of Agam and the factors that influence the market revitalization.The concept used is the revitalization theory, proposed by Gouillart and Kelly with three approaches that focus approach to the market, the creation of new business, and utilization of information technology. This research uses qualitative assessment of descriptive data. In the data collection researchers use interviewing techniques, observation and documentation by using purposive sampling method as a source of information and triangulation techniques as a source of data validity.The results showed that in the approach to market focus, Department of Cooperatives MSME Industry and Trade as well as the management market is not biased conduct revitalization program market which was highly desired by the community, to create new business department and the board has not made a working visit to improve its performance while the use of information technology board no expose or promote the market for the provision of information and tools still use conventional manner such as a letter or telephone.Keywords: Management, Revitalization, Traditional Market